Les étudiants américains et l’activité politique - Eliane Elmaleh (Revue LISA)
Students have periodically played an important role in political life as well as societal politics. While activism has subsided in the past decades, a number of students continue to be involved in political issues. This article chronicles the history of student political activism in the 20th century and focuses not only on periods when students were dramatically involved in politics, but also on less active periods. My object is to show that politics on the campus is a multi-faceted phenomenon and that, at least since the 1930s, there has been an ideological trend toward liberal activism even if conservative students have also been influential. I will also determine what has stirred students into action, the recurrent motivations and whether one can talk of a depoliticization of the university in the last few decades.